Relación entre las experiencias lógico matemáticas previas y el aprendizaje numérico de los niños y niñas al inicio del 1er grado de primaria de la I.E N°00537 “Matilde del Águila” del distrito de Rioja - Serván Grández, Lidovina (2012)
The numerical learning as one of the mathematical abilities logical of the human being only allows the use of the thought in the understanding of the objective world turning it into manageable symbolic abstractions to mental level. Taking ca re of which Ocampo says (201 0), that if the children do not have a basic understanding of the numerical system, they are going toas much have many difficulties in the reading and writing of more .and more great numbers. This situation can be directly related and to affect mental structures that demand majors structuring levels. The investigation tried to examine in the Educative lnstitution primary No the 00537 of our city profits reached in the numerical learning of the children and the children so that their results are considered in the beginning of the conduction of the mathematical logical learning in the first degree. Having as it bases the theory on the development of the mathematical thought of Piaget that prioritizes, on the education of the mathematical one, in the first years ofthe learning, the formation of the rational thought through the action with the individual and collective objects, with facts and to symbolize. Our objective was to find a possible association between previous the mathematical experiences logical, that is to say, before its enter the primary schools and the level of numerical learning obtained the children and children when initiating its first degree in the Educative lnstitution 00537 N° Matilde Del Aguila Velasquez in 2011, working with a group of 8 educational ones in whom the independent variable mediated and with a group of 90 students for the dependent variable. The investigation was fitted to a corelational descriptive design, having like research instrumental support a questionnaire to verify, from the perception of the educational ones, the level of previous experiences that the children and children and children received befare entering the primary level. The 5 the most important instruments were test destined to measure the numericallearning. They process data and they show in two parts, the first party embraces a descriptive character on the basis of a modal analysis, wholesale frequency and the second best splits comparison to both variables through an analysis coefficient correlaciona! chi once was balanced. lt was found that the teachers have a numerical appreciation of his pupils's learning level to the initiating the first primary- education grade is insufficient. lt was checked that the numerical learning in the dimensions of cardinalidad, ordinalidad, secuencialidad and measurement shows a low level As the test's aftermaths; A level among midway and height became verified only upon the encoding dimension; The playable than in broad outline the learning level prevailing he is low. The data to the submitting to the test of our hypothesis logician demonstrated the existence of a highly significant relation among the experiences himself previous mathematics and the level of the numerical learning in the boys and girls to the start of the first grade in the lnstitutión Educational N° 00537 Matilde Del Águila Velásquez of the district of Rioja.